A conceptual model of SOA-enabled business process and its empirical study - VAYVAY, ÖZALP (My University, 2012)
In today's strong competitive environment, business processes that answer customer needs are required to be flexible and agile so as not to miss business opportunities and to adopt new market requirements and new trends easily so business activity monitoring is becoming more crucial for enterprises. Although obstacles of the mass of hybrid and complex distributed systems make it an effortful issue, SOA researchers investigate solutions to eliminate them. This study proposes a conceptual model for SOA-enabled business process frameworks to identify components of such systems. The model consists of entities and their relationships represented by UML. The proposed model was tested in an international company where its business processes are well-defined and IT is seen as an important necessity for their implementation. Copyright © 2012, IGI Global.
Keywords: Business Process Management (BPM); Distributed System; Enterprise Service Bus (ESB); Eservice; Service Oriented Architecture (SOA); Web Service; Workflow